2016
DOI: 10.1016/j.hrtlng.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes in overweight heart transplant recipients

Abstract: Background There is a paucity of research examining the impact of patient weight after heart transplant (HT) on multiple clinical outcomes. Objectives The purpose of this study was to compare 9 clinical outcomes in 2 groups of HT recipients (N = 347) from 2 hospitals in the midwestern and southern United States, based on their mean body mass index (BMI) during the first 3 years post-HT, and to identify risk factors for mortality. Methods The sample was divided into 2 groups: Group 1: 108 non-overweight pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“… 83 While some studies have shown improved survival in overweight HT patients, these patients also suffered from more graft rejections, coronary artery vasculopathy and DM. 84 Because HF incidence continues to increase while organs remain in limited supply, optimal strategies for improving outcomes following HT are of utmost importance. Alyaydin et al 85 analyzed 172 HT patients for mean 13.2 years and analyzed their patients as survivors and non-survivors.…”
Section: Heart Transplantmentioning
confidence: 99%
“… 83 While some studies have shown improved survival in overweight HT patients, these patients also suffered from more graft rejections, coronary artery vasculopathy and DM. 84 Because HF incidence continues to increase while organs remain in limited supply, optimal strategies for improving outcomes following HT are of utmost importance. Alyaydin et al 85 analyzed 172 HT patients for mean 13.2 years and analyzed their patients as survivors and non-survivors.…”
Section: Heart Transplantmentioning
confidence: 99%
“…A meta-analysis has confirmed the stronger and more consistent association of the somatic (e.g., work difficulty, insomnia, fatigability) than the cognitiveaffective (e.g., sense of failure, guilt, self-dislike) symptom dimension with cardiovascular prognosis (including all-cause mortality), based on 13 prospective longitudinal studies in patients with heart disease (9); however we lack comparable data on HTx samples. (10,12,13). BMI should nevertheless be included as covariate in survival analyses because BMI values in the range indicating overweight and obesity are associated with increased mortality in never-smokers without chronic diseases (14).…”
Section: Introductionmentioning
confidence: 99%
“…51 As excessive weight gain and obesity after transplantation are associated with high risk of diabetes, graft loss, and mortality. 4,8 Further, overweight and obesity and related comorbidity ( e.g. , CAV) are important determinants of transplant recipients’ quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…8 The first 12 months following transplantation is critical as excessive weight gain during this period influences transplant outcomes such as graft rejection. 8,9 However, the magnitude of reported weight increase appears to vary substantially, and the rapidity of weight gain is unclear.…”
mentioning
confidence: 99%